EVALUASI PROSES PELAKSANAAAN KELAS IBU HAMIL DI KABUPATEN BANYUMAS - W., Septerina P.; Hastuti, Puji; Z., Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Antenatal Class (KIH) is a means of learning about the health group for pregnant women in the form of face-to-face which aims to improve the knowledge and skills of mothers about pregnancy, childbirth, postpartum care and newborn care through the use of books KIA practice. Although the program has been implemented in Banyumas district since 2012, but only 12 of 331 midwives midwives who carry class of pregnant women who have been trained as facilitators Antenatal Class. The purpose of this study was to evaluate the implementation process Antenatal Class by midwives in Banyumas district. This research is a descriptive study. The study population was a midwife who has been trained as facilitators Antenatal Class amounted to 12 people. The samples used were 12 people. The sampling technique with a total sampling. Retrieving data with primary and secondary data. The results of the research process implementation Antenatal Class 100% in both categories, means 100% incomplete. Keywords: Evaluation, Antenatal Class